1992
DOI: 10.1901/jaba.1992.25-341
|View full text |Cite
|
Sign up to set email alerts
|

Improving Social Skills and Disruptive Behavior in Children With Autism Through Self‐management

Abstract: The literature suggests that children with autism typically are unresponsive to verbal initiations from others in community settings, and that such unresponsiveness can lead to problematic social interactions and severely disruptive behavior. The present study assessed whether self-management could be used as a technique to produce extended improvements in responsiveness to verbal initiations from others in community, home, and school settings without the presence of a treatment provider. The results showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
140
0
18

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 271 publications
(167 citation statements)
references
References 22 publications
5
140
0
18
Order By: Relevance
“…Lee and Odom (1991) found that when 2 children with autism increased their engagement in social interaction with peers, stereotypic behavior decreased. Koegel, Koegel, Hurley 121 1993,26,121-132 NUMBER I (SPRING 1993) and Frea (1992) demonstrated that when the social responsivity of 4 children with autism increased, there were reductions in disruptive behavior. These recent studies provide additional grounds for continued exploration of procedures that will amplify the social interaction repertoires of children with autism.…”
mentioning
confidence: 99%
“…Lee and Odom (1991) found that when 2 children with autism increased their engagement in social interaction with peers, stereotypic behavior decreased. Koegel, Koegel, Hurley 121 1993,26,121-132 NUMBER I (SPRING 1993) and Frea (1992) demonstrated that when the social responsivity of 4 children with autism increased, there were reductions in disruptive behavior. These recent studies provide additional grounds for continued exploration of procedures that will amplify the social interaction repertoires of children with autism.…”
mentioning
confidence: 99%
“…This is despite the fact that ABA procedures have empirically demonstrated improvements for specific and overall social behaviors for high-functioning individuals diagnosed with ASD (Brodhead et al 2014;Kamps et al 1992;Koegel et al 1992;Koegel and Frea 1993;Laugeson et al 2012;Leaf et al 2015;Nikopoulous 2007;Weiss and Harris 2001).…”
Section: Does Social Thinking® Make Negative Statements About Other Pmentioning
confidence: 99%
“…Koegel et al [22] were the first researchers to study the relationship between maternal age and parenting stress. In the study, interviews were conducted with 50 mothers of children who were diagnosed with autistic disorder, with a mean age of 5.98 years old.…”
Section: Source Of Parenting Stressmentioning
confidence: 99%
“…In addition, the results indicated that stress among mothers of children younger than six years was higher than mothers of children older than six years. Overall, a review of the literature concluded that mothers younger than 30 years old with children younger than six years diagnosed with autism experienced higher levels of parenting stress [22]- [24].…”
Section: Source Of Parenting Stressmentioning
confidence: 99%